ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN DAN LOYALITAS KONSUMEN PADA BEBERAPA E-COMMERCE - Lina Dwi Uluvianti; I Made Bayu Dirgantara; Danes Quirira Octavio (Diponegoro Journal of Management, 2022)
The benefits of technology in e-commerce activities can be seen as an opportunity, especially for developing countries such as Indonesia. E-commerce does not require a physical store or investment in storage infrastructure as in the retail business sector in general, making it easier for business actors to market products without having to have a physical store. E-commerce products that are of interest to the public in shopping are beauty products. The population in this study are people who have purchased Sociolla, Watsons, and Sephora products at least once to be able to assess the factors that affect satisfaction and loyalty from consumers of Sociolla, Watsons, and Sephora products. The sampling technique used is the nonprobability sampling with a total sample of 150 respondents. The data used in this study is primary data with data collection techniques used in this study is a questionnaire. The data analysis technique used is SEM-PLS.The results of this study indicate that (1) the quality of electronic services has a positive effect on consumer satisfaction. (2) Trust has a positive effect on consumer satisfaction. (3) Satisfaction has a positive effect on consumer loyalty. (4) Satisfaction can significantly mediate the quality of electronic services on consumer loyalty. (5) Satisfaction can significantly mediate trust in consumer loyalty. Based on these results, to increase loyalty, policies and regulations are needed to optimize the quality of electronic services, trust and satisfaction.